Analysis of Forms, Challenges, and Impacts of Commercialization in Education - 'Azizi, Nur; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This research aims to analyze the forms, challenges, and impacts of commercialization in the world of education, focusing on social, economic, and academic aspects Design/Method/Approach: The research uses a qualitative approach with a literature study method. Data was collected from academic journals, policy reports, and publications of educational institutions and international organizations. Data analysis is carried out descriptively and interpretively, with the validity of the data maintained through triangulation of sources Research Finding: The results of the study identified 7 forms of commercialization of education, 6 implementation challenges, and 6 impacts arising from the commercialization of education. Forms of commercialization include privatization of educational institutions, cost recovery education, cooperation with corporations, commercialization of books and learning resources, education as digital products, exploitation of students, and commercialization of educational infrastructure Theoretical contribution/Originality: This research provides a comprehensive insight into the phenomenon of commercialization of education, systematically analyzing its various forms, challenges, and impacts. This contributes to a theoretical understanding of paradigm shifts in the modern education system Practitionel/Policy implication: Research findings can be the basis for policymakers and education practitioners in formulating strategies to balance the financial needs of educational institutions with the main mission of education as a means of developing knowledge and character Research limitation: This study was limited to a literature analysis and did not involve the collection of primary data. Follow-up studies with an empirical approach can enrich understanding of the impact of the commercialization of education in the field